Donnés concernant l’osmoréglage chez crassostrea gigas thunberg - Csernoc, Elena; Roșoiu, Natalia (Cercetări Marine - Recherches Marines, 2026)
Some data concerning the relationship between the osmotic pressure of the hemolymph and that one of the environments and the intracellular isosmotic regulation of Crassostrea gigas TH. at different salinities (8‰, 16‰, 30‰) are presented. The results confirm euryhalinity and the possibilities of osmoregulation.